PERSEPSI KONSUMEN MINUMAN ISOTONIK DI KOTA DENPASAR - GAUTAMA, I PUTU WINADA; NILA KENCANA, I PUTU EKA; SUCIPTAWATI, LUH PUTU (E-Jurnal Matematika; Volume 1, No 1, Tahun 2012DO - 10.24843/MTK.2012.v01.i01.p007, 2012)
Isotonic beverages is a drink that has a composition and the same osmotic pressure of body fluids. One of isotonic fluid and electrolyte replacement for the missing body. The main properties caused by consuming isotonic drinks, among others, to restore power after the move which can be exhausting. Denpasar City community largely has activities/jobs that drain a lot of energy. This condition is asufficient condition for both the isotonic beverage market and have many opportunities to promote its products to the city of Denpasar. Therefore, in this study wanted to know the competition some isotonic drinks brands with a range of variables examined in this case represented the city of Denpasar with Multidimensional Scaling Analysis and using Biplot Analysis of the perceptual mapping.
Keywords: MDS, biplot, isotonic beverages